Duration of breastfeeding has a positive effect on infant weight gain - Saputra, Dedi Kurniawan; Carolina, Carolina; Rusli, Riko (Universa Medicina, 2010)
With increasing maternal age hopefully the mother knows more about raising a baby and supervising their growth and development. With normal birth weight and adequate duration of exclusive breastfeeding the baby can be expected to have optimal growth and development. The goal of this historical-cohort prospective study was to analyze the relation between maternal age, infant birth weight and duration of breastfeeding on the one hand with infant weight gain on the other. The population under study were six-month-old infants in the catchment area of Pagar Gading Community Health Center, Pino Raya Region, South Bengkulu Regency. The total sample consisted of 31 six-month-old infants, selected by consecutive nonrandom sampling of subjects meeting the inclusion criteria. Statistical analysis was performed by means of the correlation-regression test. There was a significant correlation between duration of breastfeeding and infant weight gain using the correlation test (p<0.05), whilst there was no correlation of infant weight gain with maternal age (p>0.05). Furthermore, with the multiple linear regression test, duration of breastfeeding affected infant weight gain (p<0.05), but infant birth weight and maternal age had no effect (p>0.05). The conclusion of this study is that duration of exclusive breastfeeding affects infant weight gain. Breastfeeding of infants should be prolonged beyond the age of 6 months.